A study on status of neonatal transport to a level III neonatal intensive care unit - Sampathkumar, P. Sampathkumar; Gobinathan, S. (International Journal of Contemporary Pediatrics, 2018)
Background: In the past decade, great advancements in Neonatal care contributed to a fall in IMR. A further fall in IMR can only be achieved by improving the neonatal transport facilities. Hence to assess the current status of neonatal transport we undertook this study. Methods: This is a cross-sectional study of 75 neonates transported to our NICU. For all the babies, data regarding the place of birth, mode of delivery, mode of transport, etc. were collected. On admission parameters like blood glucose, temperature, CRT, SPO2, the presence of cyanosis, shock was assessed. Results: In the present study 64% of neonates came to our NICU on their conveyance. 67% of referrals from PHCs did not utilize ambulance facility. 30% of neonates had hypothermia on arrival. 35%had hypoglycemia on arrival. 15% had a low oxygen saturation on arrival. 15% had prolonged CRT on arrival. Only 8% of neonates received prior treatment. 11% babies did not have any referral slip. Only a very few had complete and proper referral advice. Conclusions: To further reduce the neonatal mortality rate, the neonatal transport facilities should be upgraded. A standard protocol should be formulated for interfacility transport. A separate fleet of neonatal ambulances well equipped and manned by trained personnel is the need of the hour.